Big Book Media with QR Codes Based on the Pancasila Student Profile to Enhance the Collaborative Character of Early Childhood Children - Nila Haryani; Yaswinda; Dadan Suryana; Farida Mayar (Jurnal Pendidikan Anak Usia Dini Undiksha, 2025)
This research is motivated by the declining trend of mutual cooperation values in early childhood due to reduced social interaction influenced by technological developments and changes in parenting patterns. This condition demands innovation in learning media that can internalize character values in a contextual and engaging manner. This study aims to analyze the validity, test the practicality, and evaluate the effectiveness of Bigbook media with QR codes based on the Pancasila Student Profile in the dimension of mutual cooperation. The study used a Research and Development approach with the Gall, Gall, and Borg model. The research subjects involved group B children at the early childhood education level. Data were collected through observation, questionnaires, and tests with instruments in the form of expert validation sheets, practicality questionnaires, and pre-tests and post-tests. Data analysis was carried out using quantitative descriptive techniques. The results of the study indicate that the developed media is categorized as valid and very practical. In addition, there was an increase in children's mutual cooperation values after using the learning media. These findings indicate that Bigbook with QR codes is effective in instilling mutual cooperation values and contributing to strengthening character education in early childhood in an innovative and relevant way to the needs of 21st-century learning.